PERUMUSAN KETENTUAN PIDANA DALAM PEMBENTUKAN PERATURAN DAERAH (Studi di Kabupaten Purbalingga) - Muhammad Fauzan; Djumadi Djumadi; Riris Ardhanariswari (Faculty of Law, Universitas Jenderal Soedirman, 2008)
Article 143 section (2) Law Number 32 Years 2004 concerning Local Government contending that by law can load six-month coop crime threat at longest or maximun Rp. 50.000.000,00 ( fifty million rupiah). While in section ( 3) the law give authority to local goverment to load the crime in the out off the this regulation. This regulation by itself give authority at local government to specify crime threat or maximal penalty. Even give crime threat besides the crime serve a sentence and penalty. The Result this research that in the reality Rule of Crime in Local Regulation in Purbalingga still not yet applied the mentioned, is even found also not clear of arrangement of rule of crime in Local Regulation Sub-Province of Purbalingga, like: boundary inexistence upper and lower in rule of crime, there is no him clarity of qualifikasi glare at alternative, or cumulative or alternatif-cumulatif, there is no him rule of attempt penalization. What for the reason this research give recommendation for this local regulation. Kata kunci: Local Government, Rule of Crime, Local Regulation